A double cavity resonant device embedded with porous material and microperforated panel. (April 2023) - Yang, Wendan; Xia, Hong; Ni, Qing-Qing
Highlights: A double cavity resonant device (DCRD) for low-frequency absorption is proposed. The DCRD offer a flexible design approach without increasing the structure's size. The air cavity and perforation ratio of MPP have a combined effect on its performance. Abstract: This research proposed a multi-band sound-absorbing device with a double resonant structure embedded with porous abrasive material and a microperforated panel. Inserting a sound-absorbing material in the Helmholtz resonator's neck and a microperforated board inside the Helmholtz resonator to form a new sound-absorption structure with two air cavities. We discussed each part's absorption coefficients to explain the sound absorption parameters and mechanism of the proposed double cavity resonant device (DCRD). For the same content of the air cavity, the sound absorption performance of the DCRD is at least 2.17 times higher than that of the Helmholtz resonance structure. The developed DCRD could almost absorb low-frequency sounds without sacrificing high-frequency performance using the microperforated panel 3. The findings show that the optimization of noise reduction, especially for low-frequency sounds, is possible through a flexible design approach without increasing the structure's size.